THE USE OF THE HOOK-JEEVES METHOD FOR THE CALCULATION OF COMPLEX NONLINEAR EQUIVALENT MAGNETIC CIRCUITS - Zagirnyak, Mykhaylo; Usatiuk, Oksana; Usatyuk, Volodymyr (Journal of Energy Technology, 2024)
The Hook-Jeeves method was used as a basis for the development of a magnetic system mathematical model suitable for carrying out engineering and optimization design calculations. It provides minimum expenditure for preparation of initial data, acceptable counting time and automatic con- vergence at a large interval of input parameter variation. The proposed model also enables highly accurate calculation of nonlinear equation systems describing complex nonlinear magnetic circuits. It is demonstrated that this approach can be used for the creation of design methods for direct current electric devices, in particular, electromagnetic separators.